Identifying the Crack Nature Using b-Value Acoustic Emission Signal Analysis - Saiful Bahari, Miera; Shahidan, Shahiron; Shukri, Mohammed; Mohd Zuki, Sharifah Salwa (Springer Nature, 2020)
Concrete is an important constituent of structures. The strength performance of the concrete decrease due to several factors. Concrete suffers from deterioration at a later stage. Early and constant identification of concrete deterioration is necessary. Nowadays, non-destructive testing (NDT) is widely used especially on continuous real-time monitoring system with minimum labor involvement. It could also be used to discriminate the different types of damage occurring in reinforced concrete (RC) beam and real structure. In this research was monitored by using Acoustic Emission testing and it have several analysis such as RA-value, b-value, intensity signal analysis and historical index. To determine the acoustic emission signals for concrete structures and cracking identification this research using b-value analysis. b-value signals analysis contain useful information about damage mechanisms. A high b-value arises due to a large number of small AE hits, it representing new crack formation and slow crack growth, whereas a low b-value indicates faster or unstable crack growth accompanied by relatively high amplitude AE in large number. Reinforced concrete beams measuring of size 150 mm 250 mm 1500 mm were used during the acoustic emission test. A four-point load test was carried out on specimens until cracking occurred. The signals generated from the equipment were used for the analysis process, and the values are compared to define and summarise type of cracking and cracking processes.